Sequential organization of birdsong: relationships with individual quality and fitness. (30th October 2020) - Zsebők, Sándor; Herczeg, Gábor; Laczi, Miklós; Nagy, Gergely; Vaskuti, Éva; Hargitai, Rita; Hegyi, Gergely; Herényi, Márton; Markó, Gábor; Rosivall, Balázs; Szász, Eszter; Szöllősi, Eszter; et al.
Abstract: Many vocalizing animals produce the discrete elements of their acoustic signals in a specific sequential order, but we know little about the biological relevance of this ordering. For that, we must characterize the degree by which individuals differ in how they organize their signals sequentially and relate these differences to variation in quality and fitness. In this study, we fulfilled these tasks in male collared flycatchers ( Ficedula albicollis ). We characterized the sequential order of syllables with a network analysis approach and studied the consistency of network variables on distinct time scales (within day, between days, and between years), and assessed their relationship with such quality indicators like age, body condition, arrival date, and fitness related proxies like survival to the next year and pairing success. We found that the syllables were associated nonrandomly with one another and both the frequency differences of consecutive syllables and the number of motif types were higher in the original than in randomized syllable sequences. Average degree and small-worldness showed considerable among-individual differences and decreasing repeatability with increasing time scale. Furthermore, we found relationships between male age and average degree among and within individuals. Accordingly, older males produce syllable sequences by using common syllables less often than younger individuals. However, the network variables showed no relationship with fitness-related variables. In conclusion, the sequential organization of birdsong has the potential to encode individual-specific characteristics, which thus could be used as signal in social interactions and thus potentially could be subject to sexual selection. Abstract : The sequential organization of song elements within the songs of the collared flycatcher can potentially function as a reliable signal and provide information about the singing male as it is consistent within individuals and correlates with male age.